Tools for Collections Management - Alexandra Van Kleef (Wimba : Jurnal Komunikasi Visual, 2014)
Paintings, sculptures, comic books, computer games, stories, it's all part of our heritage. To keep our heritage and our museum collections safe we need efficient collections management. In the last 20 years much has changed and worldwide standards for collections management were developed. One of those standards is SPECTRUM. SPECTRUM is a freely available standard that is currently used in 40 countries across the world.